System verification : proving the design solution satisfies the requirements - Grady, Jeffrey O. (Academic Press, 2016)
System Verification: Proving the Design Solution Satisfies the Requirements, Second Edition explains how to determine what verification work must be done, how the total task can be broken down into verification tasks involving six straightforward methods, how to prepare a plan, procedure, and report for each of these tasks, and how to conduct an audit of the content of those reports for a particular product entity. This process-centered book is applicable to engineering and computing projects of all kinds, and the lifecycle approach helps all stakeholders in the design process understand how the verification and validation stage is significant to them. In addition to many flowcharts that illustrate the verification procedures involved, the book also includes 14 verification form templates for use in practice. The author draws on his experience of consulting for industry as well as lecturing to provide a uniquely practical and easy to use guide which is essential reading for systems and validation engineers, as well as everyone involved in the product design process.